2013
DOI: 10.1097/bot.0b013e318251930d
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Failure After Locking Plate Fixation of Unstable Intertrochanteric Femur Fractures

Abstract: Therapeutic Level IV. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
71
2
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(79 citation statements)
references
References 23 publications
1
71
2
2
Order By: Relevance
“…In contrast to this the PFLCP act as angular stable devices and provide rigid fixation. But they are associated with a higher number of varus collapse and implant failure [13,14]. To overcome this problem the reverse-DFLCP of the contralateral side has been advocated by some authors, as it provides an added number of screw options for proximal femoral fracture fragment, resulting in a more stable construct [15][16][17].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast to this the PFLCP act as angular stable devices and provide rigid fixation. But they are associated with a higher number of varus collapse and implant failure [13,14]. To overcome this problem the reverse-DFLCP of the contralateral side has been advocated by some authors, as it provides an added number of screw options for proximal femoral fracture fragment, resulting in a more stable construct [15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…Due to higher failure rates of proximal femoral locking compression plate [13,14], some authors advocated the use of reverse distal femoral locking compression plate (reverse-DFLCP) of the contralateral side for intertrochanteric fractures, as it provided an added number of screw options for proximal femoral fracture fragments, thus resulting in a more stable construct with higher pull out resistance [15][16][17]. Clinical studies have also showed good results of reverse-DFLCP when compared to intramedullary devices [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mean follow-up in the PFLP group was 24 months (range 18-30) and 28 months (range [19][20][21][22][23][24][25][26] in the ABP group. The mean time to union was 17 weeks (range [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] in the PFLP group ( Figure 1) and 18 weeks (range 16-32) in the ABP group (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…The high rate of mechanical failure of the fixation of unstable proximal femoral fractures with proximal locking plate is expected [6]. Also, tilting of rotational order following the intramedullary nail is a fundamental problem [7].…”
Section: Discussionmentioning
confidence: 99%